Nanometer silicon negative electrode material, preparation method and application thereof, and lithium ion battery

By using nano-silicon anode material in lithium-ion batteries, forming through primary particle connection and/or agglomeration, and controlling the oxygen content through acid etching, the high oxygen content in the prior art leads to low specific capacity and low first-time efficiency. Problem, high specific capacity and high first-time efficiency battery performance is achieved.

CN119480971APending Publication Date: 2025-02-18GUIZHOU ANDA TECH ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411591098.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The high oxygen content in the negative electrode materials of existing lithium-ion batteries leads to problems such as low specific capacity and low first-time efficiency.

Method used

A nano-silicon anode material is used, which is formed by primary particles connecting and/or agglomeration, with an oxygen content of less than or equal to 13 wt%, and the oxygen content is controlled by acid etching to prepare a battery with high specific capacity and high first-time efficiency.

Benefits of technology

The lithium-ion battery negative electrode material with high specific capacity and high first-time efficiency is achieved, and high-quality negative electrode material is provided for the preparation of lithium-ion batteries with high capacity, high conductivity and high safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480971A_ABST
    Figure CN119480971A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and discloses a nanometer silicon negative electrode material, a preparation method and application thereof, and a lithium ion battery. The nanometer silicon negative electrode material is formed by connecting and / or agglomerating nanometer silicon primary particles; the oxygen content of the nanometer silicon negative electrode material is less than or equal to 13wt%. The negative electrode material disclosed by the invention has high specific capacity and first efficiency; and a high-quality negative electrode material is provided for preparing a high-capacity, high-conductivity and high-safety lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a nano silicon negative electrode material, a preparation method and application thereof, and a lithium ion battery. Background Art

[0002] Inorganic silicon materials have the characteristics of high abundance of earth elements, good safety, and easy industrialization. As a negative electrode material for lithium batteries, its theoretical specific capacity is 4200mAh·g -1 , which is the highest theoretical specific capacity among the currently known alloyed lithium storage materials. Its huge theoretical specific capacity makes it considered to be the most promising lithium battery negative electrode material. Although silicon-based materials have a large specific capacity, they will experience volume expansion (300%) during the charging and discharging process, which can easily cause the collapse of the material's main structure and the shedding and pulverization of active materials, resulting in poor cycle performance of the material. At the same time, silicon has a low intrinsic carrier concentration, which is not conducive to the effective release of battery capacity, and its cycle efficiency and conductivity are very poor, which also restricts its application in the market. In recent years, in order to make full use of silicon's high specific capacity and suppress the disadvantage of volume expansion, scientific researchers in the industry and scientific institutes have done a lot of research, laying the foundation for its industrialization process.

[0003] The oxygen content of nano-silicon has a great influence on the electrical properties. As the oxygen content in the silicon negative electrode material increases, the electrochemically active lithium storage phase (a-Si) decreases, resulting in an increase in the irreversible phases Li2O and Li4SiO4, a decrease in specific capacity, and a decrease in the initial efficiency. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem of high oxygen content in negative electrode materials in the prior art, which leads to low specific capacity and low initial efficiency of the battery, and to provide a nano-silicon negative electrode material and its preparation method and application and a lithium-ion battery. The nano-silicon negative electrode material has low oxygen content, and the battery made from it has high specific capacity and high initial efficiency.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a nano-silicon negative electrode material, wherein the nano-silicon negative electrode material comprises silicon; the nano-silicon negative electrode material is formed by connecting and / or agglomerating nano-silicon primary particles;

[0006] The oxygen content of the nano-silicon negative electrode material is less than or equal to 13 wt %.

[0007] The second aspect of the present invention provides a method for preparing a nano-silicon negative electrode material, wherein the method comprises: mixing a dispersion containing a silicon-aluminum alloy and water with an acid solution, heating the mixture to 20-100° C. at a rate of 2-20° C. / h, performing an etching reaction, filtering, washing, and drying to obtain the nano-silicon negative electrode material;

[0008] The dispersion is added to the acid solution at a rate of 4-15 kg / h;

[0009] The temperature of the acid solution is -20°C to 10°C.

[0010] A third aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises a negative electrode made of the above-mentioned nano-silicon negative electrode material.

[0011] A fourth aspect of the present invention provides an application of the above-mentioned nano-silicon negative electrode material in a lithium-ion battery.

[0012] Through the above technical solution, the nano silicon negative electrode material and its preparation method and application and lithium ion battery provided by the present invention have the following beneficial effects:

[0013] The nano-silicon negative electrode material of the present invention is formed by connecting and / or agglomerating primary particles, and its oxygen content is less than or equal to 13wt%, so that the negative electrode material of the present invention has high specific capacity and initial efficiency; and provides high-quality negative electrode materials for preparing lithium-ion batteries with high capacity, high conductivity and high safety.

[0014] The present invention adopts an acid etching method, and controls the etching rate by controlling the heating rate. At the same time, when the dispersion liquid is uniformly added to the acid solution at a specific rate, the uniformity of the addition can be better controlled, the initial reaction rate can be controlled, and then the oxygen content of the nano-silicon negative electrode material can be controlled, so that the battery manufactured has high specific capacity and high initial efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a SEM image of the nano-silicon negative electrode material provided in Example 1 of the present invention.

[0016] Figure 2 This is a SEM image of the nano-silicon negative electrode material provided in Example 2 of the present invention. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] The first aspect of the present invention provides a nano-silicon negative electrode material, wherein the nano-silicon negative electrode material comprises silicon; the nano-silicon negative electrode material is formed by connecting and / or agglomerating nano-silicon primary particles;

[0019] The oxygen content of the nano-silicon negative electrode material is less than or equal to 13 wt %.

[0020] The nano-silicon negative electrode material of the present invention is formed by connecting and / or agglomerating primary particles, and its oxygen content is less than or equal to 13wt%, so that the negative electrode material of the present invention has high specific capacity and initial efficiency; and provides high-quality negative electrode materials for preparing lithium-ion batteries with high capacity, high conductivity and high safety.

[0021] Furthermore, the oxygen content of the nano-silicon negative electrode material is less than or equal to 8wt%.

[0022] Furthermore, the oxygen content of the nano-silicon negative electrode material is less than or equal to 6wt%.

[0023] According to the present invention, the average particle size of the primary particles is 10-80 nm.

[0024] In the present invention, when the average particle size of the primary particles meets the above range, the microscopic dynamic characteristics of the nano-silicon negative electrode material can be improved, so that the negative electrode material has a high specific capacity and a high initial efficiency.

[0025] Furthermore, the average particle size of the primary particles is 20-60 nm.

[0026] According to the present invention, the D of the nano-silicon negative electrode material 50 1-2.5μm.

[0027] In the present invention, when the D of the nano-silicon negative electrode material 50 When the above range is met, the polarization degree of the nano-silicon negative electrode material can be significantly reduced, thereby improving the rate performance of the nano-silicon negative electrode material.

[0028] Furthermore, the D of the nano-silicon negative electrode material 50 1-1.5μm.

[0029] In the present invention, the nano silicon negative electrode material is a porous fiber mesh structure, which can improve the capacity and rate performance of the nano silicon negative electrode material.

[0030] According to the present invention, in the nano-silicon negative electrode material, the silicon content is greater than or equal to 83wt%.

[0031] In the present invention, when the content of silicon in the nano-silicon negative electrode material meets the above range, both the capacity and the charge and discharge efficiency of the nano-silicon negative electrode material can be taken into consideration.

[0032] Furthermore, in the nano-silicon negative electrode material, the silicon content is greater than or equal to 92wt%.

[0033] Furthermore, in the nano-silicon negative electrode material, the silicon content is 94-99wt%.

[0034] According to the present invention, the nano-silicon negative electrode material also contains aluminum.

[0035] According to the present invention, in the nano-silicon negative electrode material, the content of aluminum is less than or equal to 0.2 wt %.

[0036] In the present invention, when the aluminum content in the nano-silicon negative electrode material meets the above range, the electrical conductivity of the material can be improved, thereby improving the capacity and charge-discharge efficiency of the nano-silicon negative electrode material.

[0037] Furthermore, in the nano-silicon negative electrode material, the content of aluminum is 0.01wt%-0.15wt%.

[0038] The second aspect of the present invention provides a method for preparing a nano-silicon negative electrode material, wherein the method comprises: mixing a dispersion containing a silicon-aluminum alloy and water with an acid solution, heating the mixture to 20-100° C. at a rate of 2-20° C. / h, performing an etching reaction, filtering, washing, and drying to obtain the nano-silicon negative electrode material;

[0039] The dispersion is added to the acid solution at a rate of 4-15 kg / h;

[0040] The temperature of the acid solution is -20°C to 10°C.

[0041] The present invention adopts an acid etching method, controls the etching rate by controlling the heating rate, and further controls the oxygen content of the nano silicon negative electrode material, so that the manufactured battery has high specific capacity and high initial efficiency.

[0042] Furthermore, when the dispersion is uniformly added to the acid solution in the above manner, the uniformity of the addition can be better controlled, the initial reaction rate can be controlled, and the oxygen content of the nano-silicon negative electrode material can be reduced, so that the negative electrode material has a high capacity and initial efficiency.

[0043] In the present invention, there is no particular limitation on the method for lowering the temperature of the acid solution, and conventional acid solution cooling methods in the art can be used. Preferably, the acid solution is refrigerated at -5°C to 5°C for 2.5-4h.

[0044] Furthermore, the heating rate is 8-12°C / h.

[0045] Furthermore, the dispersion is added into the acid solution at a rate of 8-12 kg / h.

[0046] Furthermore, the temperature of the acid solution is -10°C to 5°C.

[0047] According to the present invention, the silicon-aluminum alloy is a silicon-aluminum alloy quenched by liquid nitrogen.

[0048] In the present invention, when a silicon-aluminum alloy is quenched by liquid nitrogen, the primary particles in the negative electrode material obtained by etching reaction have a smaller particle size, thereby reducing internal resistance, improving conductivity, and further improving battery performance.

[0049] In the present invention, the liquid nitrogen quenching refers to the post-processing process of the raw material silicon aluminum alloy produced before leaving the factory. In the present invention, the treatment temperature of the liquid nitrogen quenching is -190°C to -60°C, and the treatment time of the liquid nitrogen quenching is 0.5-2h.

[0050] According to the present invention, based on the total mass of the silicon-aluminum alloy, the content of silicon in the silicon-aluminum alloy is 5-40wt%.

[0051] In the present invention, when the silicon content in the silicon-aluminum alloy meets the above range, the particle size of the primary particles in the negative electrode material obtained by the etching reaction is smaller, thereby reducing the internal resistance, improving the conductivity, and further improving the battery performance.

[0052] Furthermore, based on the total mass of the silicon-aluminum alloy, the silicon content in the silicon-aluminum alloy is 15-35wt%.

[0053] According to a more preferred embodiment of the present invention, the silicon aluminum alloy is Si 20 Al 80 and / or liquid nitrogen quenched Si 30 Al 70 .

[0054] According to the present invention, the average particle size of the silicon aluminum alloy is 0.5-50 μm.

[0055] In the present invention, when the average particle size of the silicon aluminum alloy satisfies the above range, it is beneficial to obtain a negative electrode material with a small primary particle size, so that the negative electrode material has a high capacity and initial efficiency.

[0056] Furthermore, the average particle size of the silicon aluminum alloy is 1-20 μm.

[0057] According to the present invention, the acid solution is selected from at least one of a phosphoric acid solution, a nitric acid solution, a hydrochloric acid solution and a sulfuric acid solution.

[0058] According to a preferred embodiment of the present invention, the acid solution is a phosphoric acid solution.

[0059] According to the present invention, the acid concentration in the acid solution is 10-30wt%.

[0060] In the present invention, when the concentration of the acid in the acid solution meets the above range, it is beneficial to obtain a negative electrode material with a small primary particle size, so that the nano silicon negative electrode material has a high capacity and initial efficiency. For example, the concentration of the acid solution is 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt%, 30wt%, and any value in the range of any two of the above values.

[0061] Furthermore, the acid concentration in the acid solution is 13-20wt%.

[0062] According to the present invention, H in the acid solution + The molar ratio of silicon to aluminum in silicon aluminum alloy is 2.5-5.5:1.

[0063] In the present invention, when H + When the amount of aluminum in the silicon-aluminum alloy meets the above range, it is beneficial to obtain a nano-silicon negative electrode material with low oxygen content and high capacity. + The molar ratio of the aluminum to the silicon aluminum alloy can be 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, and a range composed of any two of the above.

[0064] Furthermore, the H in the acid solution + The molar ratio of silicon to aluminum in silicon-aluminum alloy is 3.5-4:1.

[0065] In the present invention, the solid content of the dispersion is 5-20wt%.

[0066] In the present invention, the dispersion method of the silicon aluminum alloy and water is not particularly limited, and any conventional dispersion method can be used.

[0067] According to the present invention, the temperature of the etching reaction is 20-100° C., and the time of the etching reaction is 12-36 hours.

[0068] In the present invention, when the etching reaction conditions meet the above range, it is beneficial for the reaction to proceed smoothly, for the degree of reaction, and for obtaining a nano-silicon negative electrode material with a high silicon content.

[0069] Furthermore, the temperature of the etching reaction is 40-70° C., and the time of the etching reaction is 20-28 hours.

[0070] In the present invention, after the etching reaction, the pH of the obtained mixed solution is 1-2, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, and any value in the range of any two of the above values.

[0071] According to the present invention, the filtration and washing process allows the pH of the washing liquid to be 4.5-7.

[0072] In the present invention, when the pH of the washing liquid meets the above range, it means that the acid in the product and the salt after etching are fully washed away, and a relatively pure nano-silicon negative electrode material is obtained. In the present invention, the pH of the washing liquid can be 4.5, 5, 5.5, 6, 6.5, 7, and any value in the range of any two of the above values.

[0073] Furthermore, the filtration and washing process makes the pH of the washing liquid be 5.5-6.5.

[0074] In the present invention, there is no particular limitation on the washing method of the mixed solution, for example, a suction filtration washing method can be adopted. Preferably, the mixed solution is suction filtered, the product after suction filtration is ultrasonically washed, and suction filtration is repeated until the pH of the washing solution after ultrasound meets the definition of the present invention.

[0075] In the present invention, there is no special limitation on the drying treatment conditions, and the drying treatment conditions of conventional negative electrode materials can be used. In order to better reduce the moisture content of nanoporous silicon after drying and prevent silicon from being oxidized during the re-drying process, the present invention preferably has a drying temperature of 150-300°C and a drying time of 20-26h. For example, the drying temperature is 150°C, 200°C, 250°C, 300°C, and any value in the range of any two of the above values. More preferably, the drying temperature is 180-250°C.

[0076] In the present invention, there is no particular limitation on the equipment used for the drying, which can be any drying equipment known to those skilled in the art. Preferably, the drying is performed in a vacuum drying oven.

[0077] According to a preferred embodiment of the present invention,

[0078] The dispersion containing silicon aluminum alloy and water is mixed with an acid solution, heated to 20-25°C at a rate of 8-12°C / h and kept warm for 0.5-1h, then heated to 40-70°C at a rate of 8-12°C / h, and an etching reaction is carried out, and the nano silicon negative electrode material is obtained by filtering, washing and drying; the dispersion is added to the acid solution at a rate of 4-15kg / h; and the temperature of the acid solution is -20°C to 10°C. In the present invention, the preferred embodiment is adopted, which is more conducive to controlling the reaction rate and allowing the acid solution to fully etch the aluminum in the silicon aluminum alloy, thereby obtaining a nano silicon negative electrode material with a lower oxygen content.

[0079] A third aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises a negative electrode made of the above-mentioned nano-silicon negative electrode material.

[0080] A fourth aspect of the present invention provides an application of the above-mentioned nano-silicon negative electrode material in a lithium-ion battery.

[0081] The present invention will be described in detail below through examples.

[0082] The test method for the oxygen content of nano-silicon negative electrode material is: X-ray photoelectron spectroscopy.

[0083] The 0.1C discharge specific capacity and 0.1C charge and discharge efficiency are measured by a battery cabinet. Specifically, under a 25°C environment, the battery is discharged to 0.005V at a rate of 0.1C, and then discharged at a constant voltage of 0.005V until the current is less than 0.05C to obtain the 0.1C discharge specific capacity; then charged to 2.0V at a rate of 0.1C to obtain the 0.1C charge capacity, and then the 0.1C charge and discharge efficiency is obtained.

[0084] The contents of silicon and aluminum in the nano-silicon negative electrode material were measured by inductively coupled plasma spectrometry.

[0085] The average particle size of the primary particles is measured by the SEM distance measurement method. The statistical average result is obtained by randomly selecting 100 single primary particles as samples in the SEM image of the nano-silicon negative electrode material. In the present invention, the average particle size of the primary particles refers to the average value of the shortest dimension of 100 single particles.

[0086] Nano-silicon anode material 50 Measured by laser particle size analyzer.

[0087] Liquid nitrogen quenching Si 20 Al 80 The brand name is ZYAlSi20 from Tianjin Zuoyuan New Material Technology Co., Ltd.

[0088] Si 20 Al 80 It is a commercial product of Hunan Ningxiang Jiweixin Metal Powder Co., Ltd. with the brand name of AlSi20 and an average particle size of 20 μm.

[0089] Si 30 Al 70 It is a commercial product of Hunan Ningxiang Jiweixin Metal Powder Co., Ltd. with the brand name of AlSi30 and an average particle size of 20 μm.

[0090] Other raw materials used in the examples and comparative examples are all commercially available.

[0091] Example 1

[0092] 0.8 kg of Si treated by liquid nitrogen quenching process 20 Al 80 Mix with 8 kg pure water and disperse by ultrasonic for 1 h to obtain uniformly dispersed Si 20 Al80 The slurry (solid content is 9wt%), phosphoric acid (acid concentration is 18wt%) was kept at 0℃ for 3h in the reactor, and Si 20 Al 80 The slurry is added to the acid solution (the dispersion addition rate is 10 kg / h), and the Si 20 Al 80 After all the slurry was added, the temperature was raised to 20°C at 10°C / h, and then heated to 65°C for 24h. + The molar ratio of silicon to aluminum is 4:1. After the etching reaction, the pH of the obtained mixed solution is 1.2. The mixed solution is filtered and ultrasonically washed until the pH of the washing solution is 5, and then the filter cake is filtered to obtain a filter cake, which is dried in a vacuum drying oven at 250°C for 24 hours to obtain a nano-silicon negative electrode material. The test results of the nano-silicon negative electrode material are shown in Table 1.

[0093] Figure 1 This is a SEM image of the nano-silicon negative electrode material provided in Example 1.

[0094] Example 2

[0095] 0.8 kg of Si 20 Al 80 Mix with 8 kg pure water and disperse by ultrasonic for 1 h to obtain uniformly dispersed Si 20 Al 80 The slurry (solid content is 9wt%), phosphoric acid (acid concentration is 18wt%) was kept at 0℃ for 3h in the reactor, and Si 20 Al 80 The slurry is added to the acid solution (the dispersion addition rate is 10 kg / h), and the Si 20 Al 80 After all the slurry was added, the temperature was raised to 20°C at 10°C / h, and then heated to 65°C for 24h. + The molar ratio of silicon to aluminum is 4:1. After the etching reaction, the pH of the obtained mixed solution is 1.2. The mixed solution is filtered and ultrasonically washed until the pH of the washing solution is 5, and then the filter cake is filtered to obtain a filter cake, which is dried in a vacuum drying oven at 250°C for 24 hours to obtain a nano-silicon negative electrode material. The test results of the nano-silicon negative electrode material are shown in Table 1.

[0096] Figure 2 This is a SEM image of the nano-silicon negative electrode material provided in Example 2 of the present invention.

[0097] Example 3

[0098] 0.8kg Si 30 Al 70Mix with 8 kg pure water and disperse by ultrasonic for 1 h to obtain uniformly dispersed Si 30 Al 70 The slurry (solid content is 9wt%), phosphoric acid (acid concentration is 18wt%) was kept at 0℃ for 3h in the reactor, and Si 30 Al 70 The slurry is added to the acid solution (the dispersion addition rate is 10 kg / h), and the Si 30 Al 70 After all the slurry was added, the temperature was raised to 20°C at 10°C / h, and then heated to 65°C for 24h. + The molar ratio of silicon to aluminum is 2.5:1. After the etching reaction, the pH of the obtained mixed solution is 1.2. The mixed solution is filtered and ultrasonically washed until the pH of the washing solution is 5, and then the filter cake is filtered to obtain a filter cake, which is dried in a vacuum drying oven at 250°C for 24 hours to obtain a nano-silicon negative electrode material. The test results of the nano-silicon negative electrode material are shown in Table 1.

[0099] Example 4

[0100] 0.8 kg of Si 20 Al 80 Mix with 8 kg pure water and disperse by ultrasonic for 1 h to obtain uniformly dispersed Si 20 Al 80 Slurry (solid content of 9wt%), phosphoric acid (acid concentration of 17wt%) was kept at 5℃ for 3h in the reactor, and Si 20 Al 80 Add acid to the slurry (the dispersion addition rate is 13kg / h), and wait for Si 20 Al 80 After all the slurry was added, the temperature was raised to 20°C at 10°C / h, and then heated to 65°C for 24h. + The molar ratio of silicon to aluminum is 3.5:1. After the etching reaction, the pH of the obtained mixed solution is 1.2. The mixed solution is filtered and ultrasonically washed until the pH of the washing solution is 5, and then the filter cake is filtered to obtain a filter cake, which is dried in a vacuum drying oven at 250°C for 24 hours to obtain a nano-silicon negative electrode material. The test results of the nano-silicon negative electrode material are shown in Table 1.

[0101] Example 5

[0102] 0.8 kg of Si 20 Al 80 Mix with 8 kg pure water and disperse by ultrasonic for 1 h to obtain uniformly dispersed Si 20 Al 80The slurry (solid content is 9wt%), hydrochloric acid (concentration of acid solution is 8wt%) is kept at 0℃ for 3h in the reactor, and Si 20 Al 80 The slurry is added to the acid solution (the dispersion addition rate is 10 kg / h), and the Si 20 Al 80 After all the slurry was added, the temperature was raised to 20°C at 10°C / h, and then heated to 65°C for 24h. + The molar ratio of silicon to aluminum is 3.5:1. After the etching reaction, the pH of the obtained mixed solution is 0.3. The mixed solution is filtered and ultrasonically washed until the pH of the washing solution is 5, and then the filter cake is filtered to obtain a filter cake, which is dried in a vacuum drying oven at 250°C for 24 hours to obtain a nano-silicon negative electrode material. The test results of the nano-silicon negative electrode material are shown in Table 1.

[0103] Comparative Example 1

[0104] 0.8 kg of Si 20 Al 80 Mix with 8 kg pure water and disperse by ultrasonic for 1 h to obtain uniformly dispersed Si 20 Al 80 The slurry (solid content is 9wt%), phosphoric acid (acid concentration is 18wt%) was kept at 0℃ for 3h in the reactor, and Si 20 Al 80 The slurry is added to the acid solution (the dispersion addition rate is 16 kg / h), and Si 20 Al 80 After all the slurry was added, the temperature was raised to 20°C at 10°C / h, and then heated to 65°C for 24h. + The molar ratio of silicon to aluminum is 4:1. After the etching reaction, the pH of the obtained mixed solution is 1.2. The mixed solution is filtered and ultrasonically washed until the pH of the washing solution is 5, and then the filter cake is filtered to obtain a filter cake, which is dried in a vacuum drying oven at 250°C for 24 hours to obtain a nano-silicon negative electrode material. The test results of the nano-silicon negative electrode material are shown in Table 1.

[0105] Comparative Example 2

[0106] 0.8 kg of Si 20 Al 80 Mix with 8 kg pure water and disperse by ultrasonic for 1 h to obtain uniformly dispersed Si 20 Al 80 The slurry (solid content is 9wt%), phosphoric acid (acid concentration is 18wt%) was kept at 0℃ for 3h in the reactor, and Si 20 Al 80The slurry is added to the acid solution (the dispersion addition rate is 18 kg / h), and Si 20 Al 80 After all the slurry was added, the temperature was raised to 20°C at 25°C / h, kept for half an hour, and then raised to 65°C and kept for 24 hours; wherein, the H + The molar ratio of silicon to aluminum is 4:1. After the etching reaction, the pH of the obtained mixed solution is 1.2. The mixed solution is filtered and ultrasonically washed until the pH of the washing solution is 5, and then a filter cake is obtained by filtration. The filter cake is dried in a vacuum drying oven at 250°C for 24 hours to obtain a nano-silicon negative electrode material.

[0107] Table 1

[0108]

[0109] Test Case

[0110] The nano-silicon negative electrode materials of Examples 1-5 and Comparative Examples 1-2 were mixed with conductive carbon black (SP) and sodium carboxymethyl cellulose (CMC) in a mass ratio of 8:1:1, slurried and coated on a copper foil, dried at 100°C and rolled with a double-roller, and then a negative electrode sheet with a diameter of 2 mm was obtained using a punching machine.

[0111] After drying the negative electrode, the CR2032 button half-cell was assembled in the UN1ab inert gas glove box of Braun, Germany. The positive electrode shell, negative electrode, electrolyte, diaphragm, lithium sheet, gasket, spring, and negative electrode shell were assembled in this order. The electrochemical performance of the CR2032 button half-cell was tested using the Wuhan Blue Electric CT2001A battery testing system with a voltage range of 0.01-2.5V. The test results are shown in Table 1.

[0112] Table 2

[0113] serial number 0.1C discharge specific capacity (mAh / g) 0.1C charge and discharge efficiency (%) Example 1 3019.8 88.75 Example 2 2941.6 86.64 Example 3 2120.5 80.56 Example 4 2782.4 85.75 Example 5 2681.5 82.51 Comparative Example 1 2253.2 78.52 Comparative Example 2 2723.4 77.96

[0114] It can be seen from the results that the nano-silicon negative electrode material prepared by the embodiment of the present invention has a low oxygen content, and the battery prepared has the characteristics of high capacity and high initial efficiency.

[0115] Figure 1 The nano silicon negative electrode material prepared in Example 1, Figure 2 It is the nano-silicon negative electrode material prepared in Example 2. It can be seen that the materials in Example 2 and Example 1 have less large particles, the particles are more uniform, and the primary particle size of the material in Example 1 is small, and the particle consistency is better, which shows that the nano-silicon negative electrode material has advantages in electrical properties such as capacity, and the battery prepared has the characteristics of high capacity and high initial efficiency.

[0116] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A nano-silicon negative electrode material, characterized in that: The nano-silicon negative electrode material comprises silicon; the nano-silicon negative electrode material is formed by connecting and / or agglomerating nano-silicon primary particles; The oxygen content of the nano-silicon negative electrode material is less than or equal to 13 wt %.

2. The nano-silicon negative electrode material according to claim 1, wherein: The oxygen content of the nano-silicon negative electrode material is less than or equal to 8wt%; And / or, the average particle size of the primary particles is 10-80 nm.

3. The nano-silicon negative electrode material according to claim 1 or 2, wherein: The D of the nano silicon negative electrode material 50 1-2.5μm; In the nano-silicon negative electrode material, the content of silicon is greater than or equal to 83wt%.

4. The nano-silicon negative electrode material according to claim 1 or 2, wherein: The nano silicon negative electrode material also contains aluminum; In the nano-silicon negative electrode material, the content of aluminum is less than or equal to 0.2wt%.

5. A method for preparing a nano-silicon negative electrode material, characterized in that: The method comprises: mixing a dispersion containing silicon aluminum alloy and water with an acid solution, heating to 20-100° C. at a rate of 2-20° C. / h, performing an etching reaction, filtering, washing and drying to obtain the nano silicon negative electrode material; The dispersion is added to the acid solution at a rate of 4-15 kg / h; The temperature of the acid solution is -20°C to 10°C.

6. The preparation method according to claim 5, wherein: The silicon-aluminum alloy is a silicon-aluminum alloy quenched by liquid nitrogen; Based on the total mass of the silicon-aluminum alloy, the silicon content in the silicon-aluminum alloy is 5-40wt%.

7. The preparation method according to claim 5 or 6, wherein: The acid solution is selected from at least one of a phosphoric acid solution, a nitric acid solution, a hydrochloric acid solution and a sulfuric acid solution.

8. The preparation method according to claim 5 or 6, wherein: The acid concentration in the acid solution is 10-30wt%; And / or, H in the acid solution + The molar ratio of silicon to aluminum in silicon aluminum alloy is 2.5-5.5:

1.

9. The preparation method according to claim 5 or 6, wherein: The temperature of the etching reaction is 20-100° C., and the time of the etching reaction is 12-36 hours.

10. The nano-silicon negative electrode material prepared by the preparation method according to any one of claims 5 to 9.

11. A lithium ion battery, characterized in that: The lithium-ion battery comprises a negative electrode made of the nano-silicon negative electrode material according to any one of claims 1-4 and 10.

12. Use of the nano-silicon negative electrode material according to claims 1-4 and 10 in lithium-ion batteries.